2007
DOI: 10.1016/j.ydbio.2007.07.022
|View full text |Cite
|
Sign up to set email alerts
|

A highly conserved Wnt-dependent TCF4 binding site within the proximal enhancer of the anti-myogenic Msx1 gene supports expression within Pax3-expressing limb bud muscle precursor cells

Abstract: The product of the Msx1 gene is a potent inhibitor of muscle differentiation. Msx1 is expressed in muscle precursor cells of the limb bud that also express Pax3. It is thought that Msx1 may facilitate distal migration by delaying myogenesis in these cells. Despite the role played by Msx1 in inhibiting muscle differentiation, nothing is known of the mechanisms that support the expression of the Msx1 gene within limb bud muscle precursor cells. In the present study we have used a combination of comparative genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…We identified several homeodomaincontaining transcription factors that are induced by Wnt signaling in the neurula stage embryo. Of these, Cdx1, Cdx4, Msx1, Msx2 and Otx2 have all been described before as direct Wnt target genes (Fujimura et al, 2009, Hussein et al, 2003, Lickert et al, 2000, Miller et al, 2007, Pilon et al, 2006, Pilon et al, 2007, Westenskow et al, 2009. We here identify two other homeodomain-containing genes, Hoxd1 and Irx3, as direct Wnt/ -catenin target genes.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…We identified several homeodomaincontaining transcription factors that are induced by Wnt signaling in the neurula stage embryo. Of these, Cdx1, Cdx4, Msx1, Msx2 and Otx2 have all been described before as direct Wnt target genes (Fujimura et al, 2009, Hussein et al, 2003, Lickert et al, 2000, Miller et al, 2007, Pilon et al, 2006, Pilon et al, 2007, Westenskow et al, 2009. We here identify two other homeodomain-containing genes, Hoxd1 and Irx3, as direct Wnt/ -catenin target genes.…”
Section: Introductionsupporting
confidence: 54%
“…In addition to the 5 genes that have already been identified as direct Wnt/-catenin target genes, i.e. Cdx1, Cdx4, Otx2, Msx1 and Msx2 (Fujimura et al, 2009, Hussein et al, 2003, Lickert et al, 2000, Miller et al, 2007, Pilon et al, 2006, Pilon et al, 2007, Westenskow et al, 2009, we identified the homeobox-containing genes Hoxd1 and Irx3 as potential novel direct target genes. In addition, we focused our attention on the Crabp2 gene since it encodes a protein that potentially feeds into the RA signaling pathway.…”
Section: Identification and Characterization Of Ap Patterning Genesmentioning
confidence: 79%
“…Several studies show that Wnts promote embryonic limb myogenesis (Anakwe et al 2003;GeethaLoganathan et al 2005GeethaLoganathan et al , 2006Takata et al 2007). However, others found that Tcf/Lef signaling inhibits differentiation of muscle progenitors (Miller et al 2007). Wnts also regulate embryonic fiber type, via canonical and noncanonical signaling (Anakwe et al 2003;Takata et al 2007).…”
Section: Pax3mentioning
confidence: 99%
“…PAX3 is downregulated when muscle tissue begins to differentiate and the muscle specific transcription factors are activated [54,56]. Ectopic expression of PAX3 prevents the myogenic differentiation of myoblasts into myotubes, which might involve the cooperation of Msx1 and Notch genes [57,58].…”
Section: Pax3 and Its Role In Development And Diseasesmentioning
confidence: 99%